Oxford Research Encyclopedia of Neuroscience 2017
DOI: 10.1093/acrefore/9780190264086.013.190
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans Feeding Behaviors

Abstract: The microscopic free-living nematode worm Caenorhabditis elegans was the first metazoan to have its genome sequenced and for many decades has served as a genetically tractable model for the investigation of neural mechanisms of behavioral plasticity. Many of its behaviors involve the detection of its food, bacteria, which are ingested and transported to the intestine by a muscular pharynx. The structure of the pharynx and the circuitry of the pharyngeal nervous system that regulates pharyngeal activity have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 112 publications
(218 reference statements)
3
20
0
Order By: Relevance
“…With this in mind, we investigated pharyngeal pumping on food and at two time points after removal from food. These data in the wild type recapitulate observations that suggest that, after food removal, worms stop pumping and slowly increase this for up to 90 min (45,46). Observations that receptor activation by modulators and neuropeptides inhibits pumping and the data reported in this study suggest that the pharynx and its embedded microcircuit allows for an intricate balance in tone.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…With this in mind, we investigated pharyngeal pumping on food and at two time points after removal from food. These data in the wild type recapitulate observations that suggest that, after food removal, worms stop pumping and slowly increase this for up to 90 min (45,46). Observations that receptor activation by modulators and neuropeptides inhibits pumping and the data reported in this study suggest that the pharynx and its embedded microcircuit allows for an intricate balance in tone.…”
Section: Discussionsupporting
confidence: 89%
“…C. elegans feeding behavior has been shown previously to change upon the presentation and removal of food (20,22), highlighting that circuits contributing to the activity of the pharynx are subject to context-dependent signaling. The observation that glutamate signaling can activate circuits to mimic feeding behavior in the OFF-food state implicates a role for this neurotransmitter pathway in the context-dependent modulation of the pharyngeal nervous system (46). Glutamatergic signaling and specific receptors therein may therefore contribute to the signaling pathways underlying context-dependent changes in C. elegans feeding behavior.…”
mentioning
confidence: 99%
“…Mechanisms by which 5HT acts rapidly on pharyngeal neural circuitry to stimulate pumping are well described (Song and Avery, 2012; Song et al, 2013; Dallière et al, 2017) and align well with the observed relationship between 5HT concentration and pump frequency in Fig. 2E.…”
Section: Resultssupporting
confidence: 79%
“…Sensory receptors that stimulate feeding are located in the head region (Dallière et al, 2017), so we tested whether head-first vs. tail-first orientation of worms in worm traps affected their responses to OP50. Table 1B compares sustained pump frequency ( t = 30–60 min after perfusate switch) in worms exposed to low or high concentrations of OP50 (O.D.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation